Some aspects of concept acquisition in history - Macrae, Michael John (Rhodes University, Faculty of Education, Department of Education, 1987)
There is concern that school history is often purposeless, taught by chalk and talk and textbook methods, giving thin and unassimilated information. At a time when subjects are under increasing scrutiny and pressure to justify their existence as relevant in the school curriculum, many of the defects inherent in the 'traditional' approach to history have made it difficult to present a forceful and valid argument for its continued inclusion as a school subject.This has led to the adoption of new approaches which are designed to get pupils more actively involved in their learning. One such approach was adopted by the Schools Council 13-16 project in Britain. It laid emphasis on the methodology of the subject and identified five ways in which history could prove to be a useful and necessary subject for adolescents to study. These were: as a means of acquiring and developing such cognitive skills as those of analysis, synthesis and judgement; as a source of leisure interests; as a vehicle for analysing the contemporary world and pupils' place in it; as a means for developing understanding of the forces underlying social change and evolutioni and, finally, as an avenue to self-knowledge and awareness of what it means to be human (Introduction, p. ii)
Keywords: History -- Study and teaching -- South Africa; History -- Study and teaching -- Testing; History -- Study and teaching -- Methodology